The European Union’s Cohesion Policy and the Economic Security of Poland - Sługocki, Waldemar (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The article presents the Polish experience resulting from implementing European Union’s cohesion policy in 2004-2006 and some experiences as well as the effects of funds from the Eu¬ropean budget in 2007-2013. The effects of structural funds implementation on the development of Polish regions was is also presented in a synthetic manner, including their effect in the socio-economic situation in Poland as a whole. Issues pertaining to the influence of European intervention into the elimination of disproportions between Poland and the richer EU states have are also touched upon. The last part of the work mentions the role of funds from the EU budget in cushioning the effects of the economic downturn.

W artykule zaprezentowano polskie doświadczenia związane z implementacją polityki spójności Unii Europejskiej w latach 2004-2006, a także doświadczenia i efekty wykorzystania funduszy europejskich w ramach budżetu na lata 2007-2013. Efekty jakie fundusze europejskie przyniosły rozwojowi polskich regionów, zostały zaprezentowane w syntetyczny sposób, z uwzględnieniem ich skutków dla sytuacji społeczno-ekonomicznej.
Polityka spójności Unii Europejskiej a bezpieczeństwo ekonomiczne Polski